Strategi Pengembangan Potensi Desa Ekowisata dan Kerajinan Perak di Desa Pampang - Ernaningsih, Zeny (Jurnal Atma Inovasia, 2021)
Pampang Village is one of the villages located in Paliyan District, Gunungkidul Regency which has its own uniqueness. The village which has an area of about 371 hectares has various potentials ranging from tourism, culinary, agro-tourism, and the most famous is silver handicraft. Therefore, the aim of the researcher is to develop and find out the various potentials of villages in Pampang Village, Paliyan District, Gunungkidul Regency, especially in the field of silver handicrafts and the development of ecotourism in Pampang Village. The data collection process uses several methods, such as literature study, namely by studying written materials from books, journals, articles, etc., as well as through interviews with resource persons who are around the residence of the research members. The results of this study regarding the potential of this Pampang village show that Pampang Village, Paliyan, Gunungkidul has various potentials that are quite unique compared to other villages in Gunung Kidul Regency.